New research methods for the analysis of fossil Anura ilia and their utility for reconstructing the palaeoenvironment of Swartkrans Cave - Brand, Ruan (Department of Archaeology, 2024)
Anura fossils are relatively common amongst microfauna assemblages but remain largely unanalysed because of a lack of expertise. This is unfortunate since Anura are effective indicators of environmental conditions as their life cycles and breeding patterns are integrally linked with temperature and rainfall. These factors, alongside having small home ranges and fast generation turnover, make Anura useful indicators of local climatic/environmental conditions. It has been hypothesized that areas with remnants of woodlands may have played an important role in human evolution by acting as refugia during periods of regional aridity and resource scarcity during the Pleistocene in Africa. In order to test this hypothesis, it is important to develop proxies that can detect these remnants. The archaeological site of Swartkrans Cave, located in the Cradle of Humankind, has yielded many samples of unanalysed Anura fossils, and has also produced the largest known sample of fossils belonging to the early Pleistocene hominin Paranthropus robustus, as well as a handful of early Homo fossils. In this study, the fossil Anura community of Swartkrans Cave is reconstructed in order to determine whether local environmental conditions were consistent with the idea of a refugium as per results of other studies of the Cradle of Humankind. Fossil assemblages from the Oldowan (Member 1, 2.2 Ma) and Acheulean (Member 3, 960 ka) deposits of Swartkrans Cave were analysed and compared as they provide snapshots of environmental conditions during periods covering the origin and extinction of P. robustus. The fossil Anura community indicates that a woodland-hydro-refugium persisted up to at least 960 ka, with the nearby Blaaubank river having been a more significant feature in the past. This analysis focuses on Anura ilia, which have several diagnostic features useful for taxonomic identification. A guide for identifying southern African Anura ilia was recently published, and this study (which presents the first application of this guide) explored the use of additional research methods, including the application of geometric morphometrics. The guide for identifying southern African Anura ilia proved to be useful, with two specific measurements proving particularly relevant regarding their application to fossil assemblages. Furthermore, this study indicates that the use of Procrustes corrections alongside this guide will greatly assist future researchers with their identifications of southern Africa Anura ilia.